Effect of biomethane substitution on combustion noise and performance of a dual fuel common rail direct injection diesel engine. Issue 6 (28th May 2022) - Abdul Hameed, Nadeem; Kurien, Caneon; Kaipakam Jaychandra, Ramesh; Mittal, Mayank
Abstract: Rising pollution levels and stringent emission regulations have raised the requirement for the utilization of alternative green fuels as a sustainable energy source for engine applications. The economic and environmental benefits of using biomethane or renewable natural gas (>95% methane) in diesel engines have made it a promising solution. Sound levels caused by combustion noise, however, is an area of concern in the early stages of engine development process, and to the best of our knowledge studies related to the impact of gaseous fuel energy share on combustion noise in dual fuel diesel engines have not been reported in the literature. In the present work, experimental research on the combustion noise of a biomethane augmented dual fuel common‐rail direct injection (CRDI) diesel engine has been carried out with a correlational design of its performance and combustion characteristics at various engine operating conditions. Comparative results on combustion and performance characteristics of different fuel compositions at various engine loads revealed that there is a better utilization of gaseous fuel at full load conditions resulting in improved power output and reduced heat transfer losses. Cylinder pressure spectra derived from recorded in‐cylinder pressure were used for carrying out the quantitative analysis of sound levels. The results suggested that an increment in methane share is effective in controlling the sound pressure levels to 95 dB (at 1.5 Newton‐meter [Nm] and 13.5 Nm loading conditions) and it is lower than the diesel‐only operational levels at all loading conditions.